The influence of gender ratios on academic careers: Combining social networks with tokenism - Schoen, Constantin; Rost, Katja; Seidl, David (PloS one, 2018)
This paper examines how gender proportions at the workplace affect the extent to which individual networks support the career progress (i.e. time to promotion). Previous studies have argued that men and women benefit from different network structures. However, the empirical evidence about these differences has been contradictory or inconclusive at best. Combining social networks with tokenism, we show in a longitudinal academic study that gender-related differences in the way that networks affect career progress exist only in situations where women are in a token position. Our empirical results further show that women not in severely underrepresented situations benefit from the same network structure as men.